Anti-spam system of new message business - Zhigang DING; Ziyu XIAO; Xuefang LI; Xiangchuan JI (Dianxin kexue)
In the background of new business requirements,the monitory point selection for new monitoring business,anti-spam system architecture,the function of the system need and the key points that should pay attention to system deployment were analyzed.Finally a set of two level monitoring system architecture and deployment guidelines for monitoring system were put forward.